Comparison of the efficacy of Letrozole versus Clomiphene Citrate among Iranian infertile females: A systematic review and meta-analysis - Zeinab Talebi Tamajani; Seyed Danial Mohammadi; Maryam Gorji; Zeinab Alimoradi (Mashhad University of Medical Sciences, 2019)
Introduction: One of the most common infertility treatment is oral medications, such as clomiphene citrate and letrozole. The clomiphene success rate is low among women with polycystic ovary syndrome and insulin resistance. However, letrozole overall success rate was high in these patients. Due to the higher price of letrozole, clomiphene is still the first-line therapy for this condition. This study aimed to systematically compare the efficacy of letrozole with clomiphene citrate in Iranian infertile females. Method: Databases, including Magiran، Medlib، SID، PubMed، Cochrane، Irandoc، IranMedex, and Google Scholar were systematically reviewed to retrieve original research articles in both Persian and English language without time limit until May 2019. The comprehensive search was conducted using Persian keywords of infertility drugs, such as clomiphene citrate, letrozole, as well as Iran, and their English equivalents. Randomized controlled trials (RCT) with full texts which compared the effect of letrozole and clomiphene citrate on infertility were included in this study. Results: Initially، 627 articles were retrieved. After removing duplicated (164) and irrelevant (463) articles، 41 full texts were further assessed in this study. Finally, 19 articles were found eligible to be included in this systematic review. In total, this study was conducted using 19 eligible RCTs involving 2638 patients. The results of the meta-analysis revealed that pregnancy rate (10%), chance of live birth (11.2%), and mean thickness of the endometrium were significantly higher in the letrozole group, compared to those in clomiphene citrate group. On the other hand, the chance of ovarian hyperstimulation syndrome (1.4%), mean number of dominant follicles (0.179), abortion (0.6%), and multiple pregnancies (4.4%) were lower in the letrozole group, compared to those in clomiphene citrate group. The results of the funnel plot and egger tests (P=0.43) confirmed no publication bias. Conclusions: Although letrozole is more expensive than clomiphene citrate، it had more promising results in achieving pregnancy with fewer side effects. However, more extensive studies are needed in this regard.